2020
DOI: 10.1111/jep.13494
|View full text |Cite
|
Sign up to set email alerts
|

Older patient and family discharge medication communication: A mixed‐methods study

Abstract: Rationale, aims, and objectives Medication discrepancies place patients discharged from hospital at risk of adverse medication events. Patient and family participation in medication communication may improve medication safety. This study aimed to examine older medical patient and family participation in discharge medication communication. Methods Two‐phased mixed‐methods study. Data were collected from July 2018 to May 2019. Phase 1 comprised observations and a questionnaire of 30 patients pre‐hospital dischar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 24 publications
2
25
0
Order By: Relevance
“…There has also been limited research investigating different health professionals' approaches to patient‐centred medication communication (Ozavci et al, 2020 ). Past studies have involved focusing on a single transition point such as discharge (Allen et al, 2018 ; Rognan et al, 2021 ; Tobiano et al, 2021 ), or on interactions with a single health professional group such as patient‐pharmacist interactions (Braaf et al, 2015 ) or patient‐doctor interactions (Kripalani et al, 2007 ). Additionally, little attention has been placed on exploring discourses used by health professionals and older patients during medication interactions.…”
Section: Introductionmentioning
confidence: 99%
“…There has also been limited research investigating different health professionals' approaches to patient‐centred medication communication (Ozavci et al, 2020 ). Past studies have involved focusing on a single transition point such as discharge (Allen et al, 2018 ; Rognan et al, 2021 ; Tobiano et al, 2021 ), or on interactions with a single health professional group such as patient‐pharmacist interactions (Braaf et al, 2015 ) or patient‐doctor interactions (Kripalani et al, 2007 ). Additionally, little attention has been placed on exploring discourses used by health professionals and older patients during medication interactions.…”
Section: Introductionmentioning
confidence: 99%
“…The involvement of family members in discharge information, such as medication and treatment adherence, has been acknowledged globally as a factor in improving patient outcomes. 13 14 Moreover, family inclusion and partnership in care strengthen patients’ readiness for discharge. 6 This is particularly important for patients with brief hospital stays, in which there is little time for HCPs to prepare patients for discharge.…”
Section: Introductionmentioning
confidence: 99%
“…The involvement of family members in discharge information, such as medication and treatment adherence, has been acknowledged globally as a factor in improving patient outcomes 13 14. Moreover, family inclusion and partnership in care strengthen patients’ readiness for discharge 6.…”
Section: Introductionmentioning
confidence: 99%
“…However, care transitions at discharge can be challenging for patients and their caregivers and a vulnerable stage in the patient pathway 17‐19 . Studies have reported that caregivers experience poor communication about medication plans and changes in medications, limited opportunities to participate in medication decisions and difficulties in following complicated medication regimens 12,20‐24 . To date, there has been a limited focus on caregivers' experience of medication management advice for people with dementia and factors that influence caregiver participation in medication plans specifically at discharge 20‐22 …”
Section: Introductionmentioning
confidence: 99%